TRANSPORT LAW AND THE CERTIFICATION PROCESS IN POLAND AND EUROPEAN UNION - Paweska, Marcin; Bugayko, Dmytro; Grigorak, Mariia; Mendrun, Robert (Proceedings of National Aviation University (archive), 2014)
Transport law in Poland is defined as a set of regulations governing not only the issues related to transport itself but also as a set of standards governing the organization of transport. The article presents brief characteristics of logistics law and regulations in Poland and European Union as well as industry enforced standards that complement the formal laws